PENERAPAN STRATEGI PEMBELAJARAN PENINGKATAN KEMAMPUAN BERPIKIR (SPPKB) UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN KEWARGANEGARAAN DI KELAS VIII SMP SWASTA FAJARMAS BAWONA’URU TAHUN PEMBELAJARAN 2021/2022 - Nurhayati Laia; Sesuaikan Sarumaha (Universitas Nias Raya, 2022)
This research is motivated by student learning outcomes that are still low. This study aims to determine the improvement of student learning outcomes through the application of the Thinking Ability Improvement Learning Strategy (SPPKB) in PPKn subjects in class VIII-A of Fajarmas Private Junior High School Bawona'uru. The research method used is a qualitative research method with the type of research is Classroom Action Research. The subjects of this study were students of class VIII of Fajarmas Private Junior High School Bawona'uru in the 2021/2022 academic year. object of research class VIII-A with a total of 23 people. The findings of the study using the Thinking Ability Improvement Learning Strategy (SPPKB) showed that the result of the percentage of completeness in processing the value of learning outcomes in the first cycle was 52.17% while the processing of learning outcomes in the second cycle was 86.95%. So it can be concluded that the Thinking Ability Improvement Learning Strategy (SPPKB) is a more effective learning strategy to improve student learning outcomes. Because the Thinking Ability Improvement Learning Strategy (SPPKB) makes students more active in the teaching and learning process. The suggestion offered by researchers is that the Thinking Ability Improvement Learning Strategy (SPPKB) should be used as an alternative in learning because it can improve student learning outcomes more actively and effectively.